High Heat Generating Granites of Kestanbol: Future Enhanced Geothermal System (egs) Province in Western Anatolia - Chandrasekharam, Dornadula; Baba, Alper; Baba, Alper; Chandrasekharam, Dornadula (TÜBİTAK - Türkiye Bilimsel ve Teknolojik Araştırma Kurumu, 2021)
Although the western Anatolian region is a foci for hydrothermal systems, this region has several high heat-generating granitic intrusive bodies that qualify to be candidates for enhanced geothermal systems (EGS). Considering the future energy requirement, carbon dioxide emissions reduction strategies, food, and water security issues, these granites appear to be the future clean energy source for the country. One such granite intrusive is located in the Kestanbol area in the western Anatolian region. The radioactive heat generation of this 28 Ma old granite varies from 5.25 to 10.38 µW/m3 with a heat flow of 92.47 to 128.61 mW/m2 . These values concur with the measured geothermal gradients and heat flow values measured from exploratory bore wells. High radon content in the thermal waters in these areas indicates interaction between the circulating fluids and the Kestanbol granite. This is for the first time evaluation of the EGS potential of granite intrusive in Turkey has been made. The Kestanbol intrusive is placed under a compressive stress regime within the Anatolian-Aegean regional tectonic framework.